Auditory Function in the Pediatric HIV/AIDS Cohort Study Adolescent Master Protocol Up Young Adults: A Pilot Study. (1st April 2023) - Torre, Peter; Zhang, Zhongli J.; Hoffman, Howard J.; Frederick, Toni; Purswani, Murli; Williams, Paige L.; Yao, Tzy-Jyun
Abstract : Background: To collect and compare selected hearing measures in a pilot study of young adults with perinatally acquired HIV (YAPHIV) and those with perinatal HIV exposure who are uninfected young adults with PHEU (YAPHEU). Setting: Cross-sectional hearing measures in YAPHIV and YAPHEU enrolled in the Pediatric HIV/AIDS Cohort Study Adolescent Master Protocol (AMP) for Participants 18 Years of Age and Older (AMP Up). Methods: Pure-tone air conduction audiometry and distortion product otoacoustic emission (DPOAE) data were collected in 1 visit. A low-frequency pure-tone average (PTA) (LFPTA, at 0.25, 0.5, 1, and 2 kHz), a speech-frequency PTA (SFPTA, at 0.5, 1, 2, and 4 kHz), and a high-frequency PTA (HFPTA, at 3, 4, 6, and 8 kHz) were calculated. Hearing loss was defined as worse ear SFPTA of ≥20 dB HL. Separate linear regression models were fit for worse ear LFPTA, SFPTA, and HFPTA to assess associations with PHIV status. DPOAE signal-to-noise ratios (SNRs) were obtained at 3 frequencies in each ear. Results: Forty-seven YAPHIV and 9 YAPHEU completed hearing testing. All adjusted mean PTAs were similar between YAPHIV and YAPHEU. Hearing loss occurred more in YAPHIV (7/47, 15.2%; 95% CI: 6.3%–28.9%), compared with YAPHEU (0/9, 0%). No associations were detected between HIV disease severity measures and worse ear SFPTA. DPOAE SNRs were similar between YAPHIV and YAPHEU. Conclusions: In this pilot study, peripheral hearing (ie, PTAs) and cochlear function (ie, DPOAEs) were similar between YAPHIV and YAPHEU. A larger study is warranted to confirm these findings.